Preconcentration of Cr(III) from Natural Water by Modified Nano Polyacrylonitrile Fiber by Methanolamine - Ali Moghimi (E-Journal of Chemistry)
Modified nano polyacrylonitrile fiber (PANF) was prepared by adding acrylic fibers to methanolamine (MMA) with different concentration solutions. The stability of a chemically modified nano polyacrylonitrile fiber especially in concentrated hydrochloric acid which was then used as a recycling and pre-concentration reagent for further uses of modified nano polyacrylonitrile fiber. The application of this modified nano polyacrylonitrile fiber for sorption of a series of metal ions was performed by using different controlling factors such as the pH of metal ion solution and the equilibration shaking time by the static technique. Cr(III) was found to exhibit the highest affinity towards extraction by these modified nano polyacrylonitrile fiber phases. The pronounced selectivity was also confirmed from the determined distribution coefficient (Kd) of all the metal ions, showing the highest value reported for Cr(III) to occur by modified nano polyacrylonitrile fiber. The modified nano polyacrylonitrile fiber for selective extraction of Cr(III) were successfully accomplished in aqueous solution as well as preconcentration of low concentration of Cr(III) (60 pg mL-1) from natural tap water with a preconcentration factor of 100 for Cr(III) and then off-line Cr(III) in water samples were determined by flame atomic absorption.